The importance of physical activity in diabetes - Miloš Purković; Danka Vukašinović; Una Radak; Miloš Maksimović (Биомедицинска истраживања, 2021)
Introduction: Obesity is becoming a global urgent issue that is considered a health problem in developed and developing countries. Obesity is a major risk factor for many non-communicable diseases such as cardiovascular diseases, type 2 diabetes mellitus (DM2), hypertension, coronary heart disease, or certain types of cancer. Physical activity is crucial for a healthy lifestyle. The aim of this study was to determine whether there is a difference in the physical activity of obese people with type 2 diabetes and obese people without type 2 diabetes. Methods: This cross-sectional study included 50 obese patients with type 2 diabetes and 57 obese patients without type 2 diabetes. All patients went through the questionnaire, anthropometric measurements and laboratory tests. Type 2 diabetes was diagnosed in accordance with the American Diabetes Association. Data on physical activity were collected using the IPAQ (International Physical Activity Questionnaire), which was composed of questions on various physical activities in the previous 7 days. Results: Activities at work and on the way to work in patients with type 2 diabetes were significantly lower compared to these activities in patients without type 2 diabetes (p <0.001). Also, leisure time physical activities were lower in people with DM2 (p = 0.001). Just in case of household chores, subjects with DM2 had more utilized metabolic equivalent (MET) minutes whose utilization rate was close to 1700 MET minutes compared to 1500 MET minutes in subjects without DM2. Conclusion: The results of this study indicate that obese subjects with DM2 are less active than obese subjects without DM2. Therefore, they should be recommended regular physical activities for at least 150 minutes per week to overcome the problem of obesity and the problem of DM2.
Keywords: physical activity; type 2 diabetes mellitus; obesity; IPAQ